ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN KONSUMEN TERHADAP FITUR AUGMENTED REALITY PADA APLIKASI E-COMMERCE SHOPEE DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Astri Purwitasari; Rozan Syaikh Ash S P; Najwa Nadia Rahma; Lano Putra Rajendra; Virdha Rahma Aulia (Jurnal Riset Sistem Informasi, 2025)
The rapid growth of e-commerce requires innovative solutions to enhance consumer engagement and overcome online shopping limitations. This research analyzes the impact of Augmented Reality (AR) technology on consumer purchase intentions in e-commerce through a quantitative approach involving 150 AR users. Using PLS-SEM analysis, this study examines the relationships between AR characteristics (interactivity, visual quality, novelty, informativeness) and consumer perceptions (enjoyment, usefulness, hedonic value) and their effects on satisfaction, attitude, and purchase intention. Results indicate that visual quality and informative aspects of AR most significantly influence consumer perceptions, while enjoyment  and  hedonic  value  significantly  affect  consumer  satisfaction  and  positive  attitudes.  These findings provide guidance for e-commerce practitioners to balance practical functionality with engaging experiences in developing AR applications as an effective marketing strategy